THE MEANING OF FINANCIAL REPORTING FOR MSMES: A PHENOMENOLOGICAL STUDY OF BEHAVIORAL ASPECTS IN COMPLIANCE AND DECISION MAKING - Rita J D Atarwaman; Muza Syahraini Prabowo; Natalia Evernande Gomies; Putri Zahra Thahir; Muhammad Arya Kabalmay (PT. Jurnal Center Indonesia Publisher, 2026)
This research is motivated by the low level of compliance of Micro, Small, and Medium Enterprises (MSMEs) in preparing financial reports in accordance with applicable accounting standards. This study aims to understand the meaning of financial reporting requirements for MSMEs, analyze behavioral aspects that influence compliance with financial reporting, and examine the use of financial reports in the business decision-making process. This study uses a qualitative approach with a phenomenological method. Data were obtained through in-depth interviews with MSMEs and analyzed thematically to explore the informants' subjective experiences. The results show that MSMEs interpret financial reporting as a simple recording tool that functions to control cash flow and business continuity, rather than as a formal administrative obligation. Compliance with financial reporting is influenced by the perception of ease, experience, and habits of business actors. Furthermore, financial reports are used only to a limited extent in business decision-making and are often combined with intuition and personal experience. These findings emphasize the need for a behavioral approach to improve the quality of MSME financial reporting.